Acute caffeine treatment increases extracellular nucleotide hydrolysis from rat striatal and hippocampal synaptosomes - Silva, Rosane Souza da (2003)
The psychostimulant caffeine promotes behavioral effects such as hyperlocomotion, anxiety, and disruption of sleep by blockade of adenosine receptors. The availability of extracellular adenosine depends on its release by transporters or by the extracellular ATP catabolism performed by the ecto-nucleotidase pathway. This study verified the effect of caffeine on NTPDase 1 (ATP diphosphohydrolase) and 5-nucleotidase of synaptosomes from hippocampus and striatum of rats. Caffeine and theophylline tested in vitro were unable to modify nucleotide hydrolysis. Caffeine chronically administered in the drinking water at 0.3 g/L or 1 g/L for 14 days failed to affect nucleotide hydrolysis. However, acute administration of caffeine (30 mg/kg, ip) produced an enhancement of ATP (50%) and ADP (32%) hydrolysis in synaptosomes of hippocampus and striatum, respectively. This activation of ATP and ADP hydrolysis after acute treatment suggests a compensatory effect to increase adenosine levels and counteract the antagonist action of caffeine.